2013
DOI: 10.1104/pp.113.224279
|View full text |Cite
|
Sign up to set email alerts
|

Terpene Down-Regulation Triggers Defense Responses in Transgenic Orange Leading to Resistance against Fungal Pathogens  

Abstract: (M.J.R., L.Z.)Terpenoid volatiles are isoprene compounds that are emitted by plants to communicate with the environment. In addition to their function in repelling herbivores and attracting carnivorous predators in green tissues, the presumed primary function of terpenoid volatiles released from mature fruits is the attraction of seed-dispersing animals. Mature oranges (Citrus sinensis) primarily accumulate terpenes in peel oil glands, with D-limonene accounting for approximately 97% of the total volatile terp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
49
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 97 publications
(125 reference statements)
1
49
0
Order By: Relevance
“…To this respect, it has been recently reported that the green leaf volatile 3-hexenyl acetate enhances defense against Fusarium graminearum in wheat (Ameye et al, 2015). In citrus, downregulation of D-limonene synthase altered monoterpene levels and also induced resistance to Penicillium digitatum infection (Rodriguez et al, 2013).…”
Section: Phytoalexinsmentioning
confidence: 99%
“…To this respect, it has been recently reported that the green leaf volatile 3-hexenyl acetate enhances defense against Fusarium graminearum in wheat (Ameye et al, 2015). In citrus, downregulation of D-limonene synthase altered monoterpene levels and also induced resistance to Penicillium digitatum infection (Rodriguez et al, 2013).…”
Section: Phytoalexinsmentioning
confidence: 99%
“…Navelina and Pineapple) accumulating highly reduced levels of the monoterpene D-limonene in the fruit peel became resistant to the bacterium Xanthomonas citri subsp citri (Xcc), to the fungus Penicillium digitatum (Pd) and to other specialized fungi. 5,14,15 D-limonene synthase downregulation was associated with constitutive upregulation of genes involved in plant innate immune response to pathogens and to increased accumulation of jasmonic acid upon challenge by the pathogen. 5 Keywords: citrus, defense, D-limonene, monoterpene, necrotroph, Penicillium digitatum, secondary metabolism, volatiles, Xanthomonas citri subsp citri Therefore, we concluded that D-limonene is required for specialized pathogens to establish infections in mature oranges.…”
mentioning
confidence: 99%
“…5,14,15 D-limonene synthase downregulation was associated with constitutive upregulation of genes involved in plant innate immune response to pathogens and to increased accumulation of jasmonic acid upon challenge by the pathogen. 5 Keywords: citrus, defense, D-limonene, monoterpene, necrotroph, Penicillium digitatum, secondary metabolism, volatiles, Xanthomonas citri subsp citri Therefore, we concluded that D-limonene is required for specialized pathogens to establish infections in mature oranges. To assess whether different D-limonene concentrations in the fruit would affect infection rate and/or symptom intensity, we have now compared the responses to either Pd or Xcc inoculation displayed by transgenic oranges with very low and medium levels of D-limonene accumulation and EV transgenic oranges with very high levels of D-limonene accumulation (comparable to wild-type (WT) oranges).…”
mentioning
confidence: 99%
See 2 more Smart Citations